Differentiate Responses of Soil Microbial Community and Enzyme Activities to Nitrogen and Phosphorus Addition Rates in an Alpine Meadow - Zi, Hongbiao; Hu, Lei; Wang, Changting (Frontiers in Plant Science, 2022)
Nitrogen (N) and phosphorus (P) are the dominant limiting nutrients in alpine meadows, but it is relatively unclear how they affect the soil microbial community and whether their effects are rate-dependent. Here, N and P addition rates (0, 10, 20, and 30 g m-2 year-1) were evaluated in an alpine meadow, and variables related to plants and soils were measured to determine the processes affecting soil microbial community and enzyme activities. Our results showed that soil microbial biomass, including bacteria, fungi, gram-negative bacteria and actinomycetes decreased along with N addition rates, but they first decreased at low P addition rates (10 g m-2 year-1) and then significantly increased at high P addition rate (30 g m-2 year-1). Both N and P addition stimulated soil invertase activity, while urease and phosphatase activities were inhibited at low N addition rate and then increased at high N addition rate. P addition generally inhibited peroxidase and urease activities, but increased phosphatase activity. N addition decreased soil pH and thus inhibited soil microbial microorganisms, while P addition effects were unimodal with addition rates, achieved through altering sedge and available P in the soil. In conclusion, our studies indicated that soil microbial communities and enzyme activities are sensitive to short-term N and P addition, and are also significantly influenced by their addition rates.